Apathy, Executive Function, and Emotion Recognition Are the Main Drivers of Functional Impairment in Behavioral Variant of Frontotemporal Dementia - Musa Salech, Gada; Lillo, Patricia; van der Hiele, Karin; Méndez-Orellana, Carolina; Ibáñez, Agustín; Slachevsky, Andrea (Frontiers in Neurology, 2022)
Background: The cognitive and neuropsychiatric deficits present in patients with behavioral variant frontotemporal dementia (bvFTD) are associated with loss of functionality in the activities of daily living (ADLs). The main purpose of this study was to examine and explore the association between the cognitive and neuropsychiatric features that might prompt functional impairment of basic, instrumental, and advanced ADL domains in patients with bvFTD. Methods: A retrospective cross-sectional study was conducted with 27 patients with bvFTD in its early stage (<2 years of evolution) and 32 healthy control subjects. A neuropsychological assessment was carried out wherein measures of cognitive function and neuropsychiatric symptoms were obtained. The informant-report Technology–Activities of Daily Living Questionnaire was used to assess the percentage of functional impairment in the different ADL domains. To identify the best determinants, three separate multiple regression analyses were performed, considering each functional impairment as the dependent variable and executive function, emotion recognition, disinhibition, and apathy as independent variables. Results: For the basic ADLs, a model that explains 28.2% of the variability was found, in which the presence of apathy (β = 0.33, p = 0.02) and disinhibition (β = 0.29, p = 0.04) were significant factors. Concerning instrumental ADLs, the model produced accounted for 63.7% of the functional variability, with the presence of apathy (β = 0.71, p < 0.001), deficits in executive function (β = −0.36, p = 0.002), and lack of emotion recognition (β = 0.28, p = 0.017) as the main contributors. Finally, in terms of advanced ADLs, the model found explained 52.6% of the variance, wherein only the presence of apathy acted as a significant factor (β = 0.59, p < 0.001). Conclusions: The results of this study show the prominent and transverse effect of apathy in the loss of functionality throughout all the ADL domains. Apart from that, this is the first study that shows that the factors associated with loss of functionality differ according to the functional domain in patients with bvFTD in its early stage. Finally, no other study has analyzed the impact of the lack of emotion recognition in the functionality of ADLs. These results could guide the planning of tailored interventions that might enhance everyday activities and the improvement of quality of life.